The Quest for Economic Stability: A Study on Swedish Stabilization Policies 1873–2019 - Fredrik N. G. Andersson (Lund University, School of Economics and Management, Department of Economics, 2020)
There is a never-ending quest for a stable economy with full employment and low inflation. Economists have suggested and policymakers have experimented with different fiscal and monetary policy regimes since at least the beginning of the industrial revolution. In this paper, we study Swedish stabilization policies through six policy regimes between 1873 and 2019. We focus on discretionary stabilization policies by estimating policy shocks. We then explore how Swedish stabilization policies have evolved over time through these shocks: how different institutional setups affected the policies and how policymakers responded to key economic events such as financial crises and wars.
Keywords: E42; E43; E52; E58; E62; E65; 330; monetary policy; fiscal policy; policy shocks; stabilization policies: financial crisis